Extracorporeal Life Support Increases Survival After Prolonged Ventricular Fibrillation Cardiac Arrest in the Rat. Issue 6 (December 2017) - Magnet, Ingrid Anna Maria; Ettl, Florian; Schober, Andreas; Warenits, Alexandra-Maria; Grassmann, Daniel; Wagner, Michael; Schriefl, Christoph; Clodi, Christian; Teubenbacher, Ursula; Högler, Sandra; Weihs, Wolfgang; Sterz, Fritz; et al.
ABSTRACT: Background: Extracorporeal life support (ECLS) for cardiopulmonary resuscitation (CPR) may increase end organ perfusion and thus survival when conventional CPR fails. The aim was to investigate, if after ventricular fibrillation cardiac arrest in rodents ECLS improves outcome compared with conventional CPR. Methods: In 24 adult male Sprague–Dawley rats (460–510 g) resuscitation was started after 10 min of no-flow with ECLS (consisting of an open reservoir, roller pump, and membrane oxygenator, connected to cannulas in the jugular vein and femoral artery, n = 8) or CPR (mechanical chest compressions plus ventilations, n = 8) and compared with a sham group (n = 8). After return of spontaneous circulation (ROSC), all rats were maintained at 33°C for 12 h. Survival to 14 days, neurologic deficit scores and overall performance categories were assessed. Results: ECLS leads to sustained ROSC in 8 of 8 (100%) and neurological intact survival to 14 days in 7 of 8 rats (88%), compared with 5 of 8 (63%) and 1 of 8 CPR rats. The median survival time was 14 days (IQR: 14–14) in the ECLS and 1 day (IQR: 0 to 5) for the CPR group ( P  = 0.004). Conclusion: In a rat model of prolonged ventricular fibrillation cardiac arrest, ECLS with mild hypothermia produces 100% resuscitability and 88% long-term survival, significantly better than conventional CPR.